2023
DOI: 10.3390/ijms24129918
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cell Subpopulations Are Associated with Morphological Features of Breast Ductal Carcinoma In Situ

Joanna Szpor,
Joanna Streb,
Anna Glajcar
et al.

Abstract: Ductal carcinoma in situ (DCIS) is the preinvasive form of breast cancer (BC). It is disputed whether all cases of DCIS require extensive treatment as the overall risk of progression to BC is estimated at 40%. Therefore, the crucial objective for researchers is to identify DCIS with significant risk of transformation into BC. Dendritic cells (DC) are professional antigen presenting cells and as such play a pivotal role in the formation of immune cells that infiltrate in breast tumors. The aim of this study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Additionally, we demonstrated that DC-LAMP + DCs are prevalent in larger tumors with higher nuclear grade and lower expression of ER and PR. Consequently, DCIS with features of neoductgenesis were infiltrated with larger amounts of DC-LAMP + DCs [36]. However, our current findings suggest that the population of DC-LAMP + DCs could not be incorporated as the biomarker of the response to NAC in BC.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Additionally, we demonstrated that DC-LAMP + DCs are prevalent in larger tumors with higher nuclear grade and lower expression of ER and PR. Consequently, DCIS with features of neoductgenesis were infiltrated with larger amounts of DC-LAMP + DCs [36]. However, our current findings suggest that the population of DC-LAMP + DCs could not be incorporated as the biomarker of the response to NAC in BC.…”
Section: Discussionmentioning
confidence: 61%
“…We already established that pDCs were more prevalent in high-grade BC approached without any neoadjuvant treatment [37]. Interestingly, our previous findings showed that CD123 + pDCs density was particularly increased in higher grade ductal carcinoma in situ (DCIS) showing features of neoduct-genesis [36].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation